In Defense of a Complex Notion of Subject in Organizational Studies - Magalhães, Alex Fernandes; Saraiva, Luiz Alex Silva (Organizações & Sociedade, 2022)
This essay reflects on the need to expand the complexity of the notion of subject in the critical approaches used in organizational studies and to contribute with a new perspective on the human attribute in collective issues based on a new concept: the concrete procedural subject. The human and social sciences are faced with the challenge of delimiting their object of study (human beings in their manifestations) without excluding the biological, social, historical, and psychological dimensions that are inherent to them, thus avoiding reductionism. It is believed that this complex perspective is relevant to analyses of socio-organizational spaces since we take the subject as a fundamental analytical unit to understand organizational dynamics. Organizations emerge from the interrelationships between subjects, expanding, structuring, and institutionalizing themselves. Therefore, the subject and organization are inseparable, and dichotomies must be avoided in favor of knowledge production in organizational studies and other correlated areas. Based on a critical analysis and adopting a multifaceted and plural approach, with contributions from psychoanalysis, sociohistorical psychology, and post-structuralism, all of which address the complexity of the human being, this essay presents a notion of subject that is contradictory and fluid, which are the marks of its procedurality in contemporary times and the foundation for understanding the complex socioorganizational dynamic and its phenomena.